Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


1/x=1/(sqrt3+1)=1/( sqrt3+1 x (sqrt3-1)/(sqrt3-1) = (sqrt3-1)/2 
Cubing both the side we get
(x+1/x)^3 = x^3 + (1/x)^3 + 3(x + 1/x)
={sqrt3+1+(sqrt3-1)/2)}^3 = x^3 +(1/x)^3 + 3(sqrt3+1+(sqrt3-1)/2)
={(3sqrt3+1)/2}^3=x^3 + (1/x)^3 + 3{(3sqrt3+1)/2)
={(3sqrt3+1)/2}^3 - {3{(3sqrt3+1)/2)}
= (81sqrt3+1)/8-{(9sqrt3+3)/2}
here "-" sign will change signs after the bracket 
taking lcm

0 0 0
x= (sqrt 3+1)/2 so 1/x becomes 2/(sqrt 3+1) but i understood the process. thanks in helping me
nope 1/x becomes (sqrt3-1)/2
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts